Outcomes of diagnosed COVID-19 cancer patients: concerning results of a systematic review. (24th November 2021) - Nahshon, C.; Segev, Y.; Schmidt, M.; Bar-noy, T.; Ostrovsky, L.; Lavie, O.
Abstract : Since the outbreak of coronavirus disease 2019 (COVID-19), malignancy was shown to be prevalent in COVID-19 patients. This systematic review's searches were conducted in MEDLINE(R), Embase, Web of Science, and Scopos. Considered for inclusion were all reports on outcomes of cancer patients diagnosed with COVID-19. A total of 1099 references were identified through database searching and manual search. Finally, 17 references comprising 88 cancer patients, diagnosed with COVID-19, were included. Prevalence of cancer patients with COVID-19 was shown to range from 0.9% to 3%. The evidence suggested a severe clinical course of 50.6% in COVID-19 diagnosed cancer patients and a mortality rate of 34.5%. Subgroup analysis according to recent anti-cancer treatment showed a similar pattern, with the most concerning results in patients receiving recent immunotherapy/immunosuppressive treatment. COVID-19 morbidity and mortality among cancer patients should be reduced by consideration of testing asymptomatic COVID-19 cancer patients, reduction of hospital visits, and consideration of anti-cancer treatment.